Analysis of Factors Influencing Teacher Performance at Public Elementary Schools in Sosopan Subdistrict - Astri Novia Siregar; Aswin Bancin (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
This research has a fundamental objective, which is to identify and analyze the influential factors on teacher performance within an educational context. The methodology employed in this study is a quantitative approach, aimed at collecting measurable data for statistical analysis. The research was conducted in the Sosopan Subdistrict, Padang Lawas District, with a focus on public schools. The studied population encompassed all teachers in the Elementary Public Schools (SDN) within the area, with a sample size of 129 teachers participating. To ensure the validity of the utilized instruments, a validity test was conducted using the Product Moment formula, while the instrument's reliability was examined through the Cronbach's Alpha formula. The findings of this research reveal that the main factors influencing teacher performance in the SDN of Sosopan Subdistrict are work culture, job satisfaction, and work motivation. Through multiple regression analysis, it becomes evident that these factors bear a significant relationship with teacher performance. This underscores the importance of a positive working environment, adequate satisfaction levels, and high motivational drive in enhancing the performance of teachers within the educational milieu. These findings offer valuable insights for the development of strategies and policies aimed at improving the quality of education in local schools.